Development of Electronic Flipbook Realistic Mathematics Education of Youtube-based to Increase Student Attractiveness - Teti Trisnawati; Stevanus Budi Waluya; Nuriana Rachmani Dewi; Dwi Yulianto (Universitas Negeri Semarang, 2022)
Abstract. The lack of use of learning media in learning makes students less enthusiastic about participating in learning. In learning, students also need learning media that can help them understand the material repeatedly so it is necessary to develop learning media such as interactive flipbook electronic teaching materials based on YouTube. This study aims to produce interactive flipbook electronic teaching materials based on SPLDV class VIII material that has been tested for validity and reliability. This research is development research using the ADDIE model. The subjects in this study were: 2 material experts, 2 media experts, and 30 student responses. The data collection method uses an instrument in the form of a rating scale with an assessment sheet for the validity of interactive flipbook electronic teaching materials based on SPLDV material. The data analysis techniques used are qualitative analysis and quantitative analysis. The data is analyzed using the mean formula to obtain the average of the scores. The research results obtained are interactive flipbook electronic teaching materials based on youtube SPLDV material received an assessment of 85.50% from media experts, 85.83% from material experts, and 85.73% from users or students. So it can be concluded that the interactive flipbook electronic teaching material based on Youtube SPLDV material is very feasible in MTs Kun Karima.